Hydrogen sulfide inhibits homocysteine-induced endoplasmic reticulum stress and neuronal apoptosis in rat hippocampus via upregulation of the BDNF-TrkB pathway - Wei, Hai-jun; Xu, Jin-hua; Li, Man-hong; Tang, Ji-ping; Zou, Wei; Zhang, Ping; Wang, Li; Wang, Chun-yan; Tang, Xiao-qing (Acta pharmacologica Sinica, 2014)
Aim： Homocysteine （Hcy） can elicit neuronal cell death, and hyperhomocysteinemia is a strong independent risk factor for Alzheimer’s disease. The aim of this study was to examine the effects of hydrogen sulfide （H2S） on Hcy-induced endoplasmic reticulum （ER） stress and neuronal apoptosis in rat hippocampus. Methods： Adult male SD rats were intracerebroventricularly （icv） injected with Hcy （0.6 μmol/d） for 7 d. Before Hcy injection, the rats were treated with NaHS （30 or 100 μmol·kg^-1·d^-1, ip） and/or k252a （1 μg/d, icv） for 2 d. The apoptotic neurons were detected in hippocampal coronal slices with TUNEL staining. The expression of glucose regulated protein 78 （GRP78）, C/EBP homologous protein （CHOP）, cleaved caspase-12, and BDNF in the hippocampus were examined using Western blotting assays. The generation of H2S in the hippocampus was measured with the NNDPD method. Results： Hcy markedly inhibited the production of endogenous H2S and increased apoptotic neurons in the hippocampus. Further-more, Hcy induced ER stress responses in the hippocampus, as indicated by the upregulation of GRP78, CHOP, and cleaved caspase-12. Treatment with the H2S donor NaHS increased the endogenous H2S production and BDNF expression in a dose-dependent manner, and significantly reduced Hcy-induced neuronal apoptosis and ER stress responses in the hippocampus. Treatment with k252a, a specific inhibitor of TrkB （the receptor of BDNF）, abolished the protective effects of NaHS against Hcy-induced ER stress in the hippocampus. Conclusion： H2S attenuates ER stress and neuronal apoptosis in the hippocampus of Hcy-treated rats via upregulating the BDNF-TrkB pathway.